Peningkatan Komitmen Terhadap Profesi Guru Melalui Penguatan Kepemimpinan Transformasional Dan Komunikasi Interpersonal - Setiawan, Asep Purwa; Wulandari, Farida; Sumardi, Sumardi (Universitas Pakuan, 2024)
INCREASING COMMITMENT TO THE TEACHER PROFESSION THROUGH STRENGTHENING TRANSFORMATIONAL LEADERSHIP AND INTERPERSONAL COMMUNICATION In general, this research aims to increase commitment to the profession among public elementary school teachers in Cileungsi District, Bogor Regency, through efforts to develop transformational leadership and interpersonal communication variables by identifying the strengths of the relationship between these variables. The method used in this research is a survey method with a correlation approach. The population in this study was 826 teachers from 54 state elementary schools in Cileungsi District, Bogor Regency. Of the 826 State Elementary School teachers in Cileungsi District, Bogor Regency, 270 people would be sampled. The research results show a positive and significant relationship between transformational leadership and interpersonal communication together with commitment to the profession, with a correlation value of ry1.2 of 0.669, which means the relationship is strong. The contribution of transformational leadership and interpersonal communication to commitment to the profession obtained a Coefficient of Determination (KD) value of 0.448 with very strong criteria, which means 44.8%.